APLIKASI INFORMASI RUTE ANGKUTAN UMUM DI SEMARANG BERBASIS ANDROID (Information Technology and Telematics, 2013)
Semarang city is included in the big city that has a lot of public transport operations. A large number of public transport and make the most of the growing community at a loss to determine what kind of public transport and routes to be addressed. It is necessary to design an application that can route information to solve the problem. The purpose of this research is to design and produce a public transport route information applications in Semarang-based android users can access anywhere. In this study, the authors use the waterfall development method. To use the programming language Java programming language and MySQL database eclipse. This research resulted in a public transport route information applications that can provide trajectory information and the desired public transport users within the scope of the city of Semarang. This application can run on mobile devices that have android operating system that uses GPS to determine the position of facility users and the internet as a liaison to the server. In this application development using the Google Map API to display the map. This application is expected to assist the user in providing the information needed. Keywords: Application route public transit, public transportation route Semarang, Android Applications